Age-related differences in physical activity and depressive symptoms among 10−19-year-old adolescents: A population based study. (January 2017) - Baldursdottir, Birna; Valdimarsdottir, Heiddis B.; Krettek, Alexandra; Gylfason, Haukur Freyr; Sigfusdottir, Inga Dora
Abstract: Objectives: The aim of this study was to examine age- and gender-related patterns of PA and depressive symptoms among students through their adolescent years. Design: Data from three population-based surveys were analysed to determine levels of moderate- to vigorous-intensity PA (MVPA), participation in organized sports and depressive symptoms among 10−19-year-old adolescents. Method: Questionnaires assessing PA and depressive symptoms were administered to 32 860 students in compulsory and upper-secondary schools in Iceland. Results: As age increased, depressive symptoms increased and PA decreased with over half of the adolescents in upper-secondary schools not achieving recommended daily PA. There were gender differences in PA and depressive symptoms with girls being less active and reporting higher levels of depressive symptoms than boys. MVPA was associated with lower levels of depressive symptoms among both genders while organized sports had more impact on depressive symptoms among girls. Conclusions: To our knowledge, this study is the first to simultaneously examine patterns of PA and depressive symptoms among students through their adolescent years. Our findings show that the decrease in PA and increase in depressive symptoms is most pronounced around the transition from compulsory to upper-secondary school, or around the age of 15–16. Thus the findings provide important information about when to tailor public health efforts to reduce the burden of depressive symptoms among adolescents, for example by employing PA interventions. Highlights: We simultaneously examine patterns of PA and depressive symptoms in adolescence. With increasing age, PA decreases and depressive symptoms increase. Most pronounced differences seen around the age of 15–16. MVPA is associated with lower levels of depressive symptoms among boys and girls. Girls benefit more than boys from participation in organized sports.